Effects of different deodorization methods on the oxidation of sterol components in rice bran oil. (15th March 2023) - Yu, Dianyu; Dong, Tianyu; Zhang, Le; Zhou, Xiaonan; Wang, Liqi; Yang, Fuming; Liu, Tianyi
Highlights: Deodorization of water vapor contributed to the loss of oil and phytosterols. Deodorization with nitrogen instead of water vapor improved phytosterols retention. Nitrogen deodorization promoted the formation of phytosterol esters. Nitrogen deodorization reduced the formation of phytosterol oxides products. Abstract: Rice bran oil contains a significant quantity of phytosterols that have various active functions and are natural active substances beneficial to humans. It is well known that deodorization during refining affects the quality of rice bran oil. However, changes in phytosterols fraction caused by stripping with nitrogen compared to water vapor remain unexplored. We measured phytosterols in rice bran oil after deodorization with nitrogen and water vapor. The variations in sitosterol fraction, which accounts for the highest percentage of phytosterols in rice bran oil, were analyzed by Gas chromatography (GC), Fourier transform infrared spectrometer (FTIR), and Nuclear magnetic resonance (NMR). Results showed that using nitrogen as the stripping gas was more suitable for deodorization. It promoted the formation of phytosterol esters, reduced the production of phytosterol oxidation products and improved the oil quality. This study provides a theoretical basis for improving the industrial production quality of rice bran oil.